Etiudy Andrzeja Brzozowskiego - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2011)
Andrzej Brzozowski’s Film Etudes Marek Hendrykowski presents in his study the earliest fiction and documentary films made by Andrzej Brzozowski (1932-2005), excellent Polish filmmaker, 1971-2005 professor of the famous Film School in Łódź (PWSFTviT). “Sunflowers” (1953), “Escape” (1954/55), “Legend” (1957), “Jazz Talks” (1957) – these short films, preserved in the collection of Film School Archive, are almost unknown for wider audience in Poland and abroad. In the second part of his study Hendrykowski gives also an accessible overview of the historical evolution of the filmmaker through the close examination of another two outstanding short films made by him: By the Railway Track (1963) and Medallions (1966). Last two were adaptations of short stories written in 1945 by Zofia Nałkowska, a masterpiece of antinazi world lterature. The article deals with the most important values and close-reading thematic and stylistic areas of Brzozowski’s early works: those developing in the 1950’s and early 1960’s but having deep impact in the poetics of academic short film in Poland, whose form and course they have fundamentally redirected.